IoT-Based Real-Time River Monitoring and Early Flood Warning Using ESP32 and HC-SR04 - Asri Mulyani; Dede Kurniadi; Rizki Esa Saputra (Journal of Novel Engineering Science and Technology, 2026)
Floods remain one of the most frequent and destructive natural disasters in Indonesia, primarily caused by rising river water levels. This study presents a prototype of an IoT-based river water level monitoring system using an HC-SR04 ultrasonic sensor, an ESP32 microcontroller, and the Blynk platform for real-time monitoring and alerting. The system classifies water levels into three categories: safe, alert, and danger, triggering local alarms (buzzers) and smartphone notifications accordingly. Evaluation results show a high sensor accuracy of up to 99.7%, with a notification delay averaging 1.2 seconds and a buzzer response time of less than 0.5 seconds. The system has been tested through black box testing and field simulations and has shown reliable performance for early flood warnings. These findings demonstrate the system’s potential in enhancing flood preparedness, particularly in vulnerable communities. Future enhancements include deploying waterproof sensors and integrating additional alert platforms such as SMS or sirens.